Ramy interpretacyjne zmysłów we wczesnych i późnych powieściach Jerzego Pilcha = The interpretative framework of the senses in the early and late novels by Jerzy Pilch - Kładoczny, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article is devoted to the conceptualization of the senses by Jerzy Pilch included in the interpretation framework of each of them. Thanks to the research, one can see how the hierarchy of the author's perceptions is presented and which ranges dominate in them. The material comes from Jerzy Pilch's two early novels "Spis cudzołożnic" ["List of adulteers"] (1993) and "Inne rozkosze" ["Other pleasures"] (1995) and the last two "Zuza albo czas oddalenia" ["Zuza or the time of distance"] (2015) and "Portret młodej wenecjanki" ["Portrait of a young Venetian woman"] (2017).
Keywords: rama interpretacyjna; konceptualizacja; zmysły; powieść; interpretation framework; conceptualization; senses; novel